Replacement of the Nasal Dorsum with a Diced Cartilage Glue Graft - Tasman, Abel-Jan (Facial Plastic Surgery, 2019)
The reconstruction of the nasal dorsum after a hump resection is challenging if narrowing of the nose is to be avoided, the nasal skin is very thin, and the nasal bones are short. This report describes the replacement of the bony and cartilaginous nasal dorsum after resection with an anatomically shaped dorsal replacement graft of diced cartilage in fibrin glue. The technique is illustrated with a clinical case and sonographic morphometry of the nasal dorsum and tip. A modification of the diced cartilage glue graft for thin-skinned patients is presented.
Keywords: rhinoplasty; endonasal; dorsal reconstruction; open roof; diced cartilage glue graft